The Wnt signaling cascade in the pathogenesis of osteoarthritis and related promising treatment strategies - Cheng, Jinchao; Li, Min; Bai, Ruijun (Frontiers in Physiology, 2022)
Osteoarthritis (OA) is the most prevalent joint disease, characterized by the degradation of articular cartilage, synovial inflammation, and changes in periarticular and subchondral bone. Recent studies have reported that Wnt signaling cascades play an important role in the development, growth, and homeostasis of joints. The Wnt signaling cascade should be tightly regulated to maintain the homeostasis of cartilage in either the over-activation or the suppression of Wnt/β-catenin, as this could lead to OA. This review summarizes the role and mechanism of canonical Wnt cascade and noncanonical Wnt cascade experiments in vivo and in vitro. The Wnt cascade is controlled by several agonists and antagonists in the extracellular medium and the cytoplasm. These antagonists and agonists serve as key molecules in drug intervention into the Wnt pathway and may provide potential approaches for the treatment of OA. However, the complexity of the Wnt signaling cascade and the pharmaceutical effects on its mechanism are still not fully understood, which forces us to conduct further research and develop efficient therapeutic approaches to treat OA.